Peran Kualitas Laba dalam Memediasi Hubungan Stakeholder Engagement dan Board Gender Terhadap Nilai Perusahaan - I Komang Agus Trisna Adi Prayoga; Putu Purnama Dewi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Stakeholder engagement and board gender are important aspects of corporate governance that are expected to influence firm value, particularly through the improvement of earnings quality. However, the indirect relationship between these factors and firm value has not been widely examined, especially in the Indonesian mining industry, which faces high social, environmental, and governance risks. Mining companies listed on the Indonesia Stock Exchange during the 2020–2024 period experienced fluctuations in firm value, which are presumed to be influenced by stakeholder engagement practices and board gender composition. This study uses the population of all mining companies listed on the Indonesia Stock Exchange, with samples selected using a purposive sampling method. Data analysis is conducted using panel data regression and mediation analysis. The results indicate that stakeholder engagement and board gender have a positive and significant effect on firm value, both directly and indirectly through earnings quality. Earnings quality is proven to be a significant mediating variable. This study contributes empirical evidence on the role of earnings quality as a mediating mechanism in the relationship between corporate governance practices and firm value in the mining sector.